Seasonal variations in biochemical and stable isotope compositions of particulate organic matter in two contrasting temperate coastal lagoons of Korea - Lee, Dong-Young; Kwak, Jung Hyun; Park, Tae Hee; Kang, Hee Yoon; Kim, Dongyoung; Hwang, Sungmin; Park, Hyun Je (Frontiers in Marine Science, 2022)
The geomorphology of coastal lagoons has an important effect on the hydrological balance between fresh water and seawater, which exhibit a wide range of salinity from nearly fresh water to hypersaline water. The present study aimed to characterize seasonal biogeochemical properties of suspended particulate organic matter (POM) in response to environmental variability driven by hydrological dynamics in contrasting coastal lagoon systems. We selected two lagoons distinguished by their geomorphological features, a permanently open artificial lagoon (Gyeongpoho) and an intermittently open natural lagoon (Hyangho), analyzed environmental characteristics, and compared the seasonal differences in the biochemical compositions of POM. Variations in temperature and precipitation in both lagoons showed the characteristics of a typical monsoon climate but variation in salinity differed 6.5−35.0 in Gyeongpoho and 1.1−10.8 in Hyangho. A self-organizing map analysis using the environmental data revealed that the spatiotemporal variations in salinity and nutrient concentrations differed significantly between the two lagoon systems, indicating a difference in hydrologic connectivity between lagoons and marine systems. Furthermore, a canonical correlation analysis highlighted that the POM properties differed according to physicochemical factors. The differing environmental conditions may affect the spatial and temporal variations in organic matter composition, resulting in significant differences in the biochemical composition of POM between two lagoon systems. Overall, this information provides insight into the origin and transport process of POM under changing coastal lagoon environments caused by climatic and human activities.